Community Prosecution: Planning & Implementation Workbook - American Prosecutors Research Institute’s National Center for Community Prosecution (My University, 2016)
The Community Prosecution Planning and Implementation Workbook contains forms with individualized instructions that can be used as a resource for jurisdictions planning and implementing community prosecution initiatives. The planning forms were developed to guide you through the planning process at the beginning stages of your community prosecution effort and the implementation forms were developed to assist you in carrying out your plans. The information documented on the forms will be invaluable to your program in several ways. Taking the time to accurately and thoughtfully complete the forms will enable your team to lay the foundation for a focused and realistic program and once the program is up and running, they will help you monitor how things are going. The workbook will provide your team with the necessary tools to monitor the accomplishments and milestones reached by your program. Clearly defined and documented information should also facilitate the completion of grant reports and applications. (palabras claves: persecución penal inteligente, investigación penal, ministerio público, comunidad)